International Student Expectations: Career Opportunities and Employability - Nilsson, Per A.; Ripmeester, Nannette (Journal of International Students, 2016)
Are mobile students expecting an international experience to have an impact on their career? This was one of the questions in a global survey, with over 150,000 respondents. The survey results showed that the transition from education to the world of work is of increasing importance for students. How to find a job upon graduation is apparently a big concern for current-day students, which dictates their international educational choices to a large extent. Moreover, are there differences between Europe and the rest of the world when it comes to student’s expectations of employability? This study found that opportunities for work upon graduation and earning money when studying matter more for non-European students.